Ca2+ channel clustering with insulin-containing granules is disturbed in type 2 diabetes - Gandasi, NR; Yin, P; Riz, M; Chibalina, MV; Cortese, G; Lund, PE; Matveev, V; Rorsman, P; Sherman, A; Pedersen, MG; Barg, S (American Society for Clinical Investigation, 2017)
Loss of first-phase insulin secretion is an early sign of developing type 2 diabetes (T2D). Ca2+ entry through voltage-gated L-type Ca2+ channels triggers exocytosis of insulin-containing granules in pancreatic β cells and is required for the postprandial spike in insulin secretion. Using high-resolution microscopy, we have identified a subset of docked insulin granules in human β cells and rat-derived clonal insulin 1 (INS1) cells for which localized Ca2+ influx triggers exocytosis with high probability and minimal latency. This immediately releasable pool (IRP) of granules, identified both structurally and functionally, was absent in β cells from human T2D donors and in INS1 cells cultured in fatty acids that mimic the diabetic state. Upon arrival at the plasma membrane, IRP granules slowly associated with 15 to 20 L-type channels. We determined that recruitment depended on a direct interaction with the synaptic protein Munc13, because expression of the II-III loop of the channel, the C2 domain of Munc13-1, or of Munc13-1 with a mutated C2 domain all disrupted L-type channel clustering at granules and ablated fast exocytosis. Thus, rapid insulin secretion requires Munc13-mediated recruitment of L-type Ca2+ channels in close proximity to insulin granules. Loss of this organization underlies disturbed insulin secretion kinetics in T2D.